Serum Resistin and Kidney Function: A Family-Based Study in Non-Diabetic, Untreated Individuals - Menzaghi, Claudia (Public Library of Science, 2012)
BACKGROUND: High serum resistin levels have been associated with kidney dysfunction. Most of these studies have been carried out in individuals with severe kidney impairment, diabetes, cardiovascular disease and related treatments. Thus, the observed association might have been influenced by these confounders. Our aim was to study the relationship between serum resistin, urinary albumin/creatinine ratio (ACR) and glomerular filtration rate (GFR) in a family-based sample, the Gargano Family Study (GFS) of 635 non diabetic, untreated Whites. METHODS: A linear mixed effects model and bivariate analyses were used to evaluate the phenotypic and genetic relations between serum resistin and both ACR and eGFR. All analyses were adjusted for sex, age, age squared, BMI, systolic blood pressure, smoking habits and physical exercise. RESULTS: After adjustments, resistin levels were slightly positively associated with ACR (β±SE = 0.049±0.023, p = 0.035) and inversely related to eGFR (β±SE = −1.43±0.61, p = 0.018) levels. These associations remained significant when either eGFR or ACR were, reciprocally, added as covariates. A genetic correlation (ρg = −0.31±0.12; adjusted p = 0.013) was observed between resistin and eGFR (but not ACR) levels. CONCLUSION: Serum resistin levels are independently associated with ACR and eGFR in untreated non-diabetic individuals. Serum resistin and eGFR share also some common genetic background. Our data strongly suggest that resistin plays a role in modulating kidney function.